Feasibility of Bitterness Reduction in Bitter Gourd (Momordica Charantia) Dried Powder By Blanching, Enzyme, and Wall Material - N. P. Minh (Journal of Global Pharma Technology, 2016)
Momordica charantia, commonly known as bitter gourd has been traditionally used to treat diabetes and its complications. Several medicinal properties of the bitter gourd have been studied such as anti-diabetic, anti-ulcerogenic, antimutagenic, antioxidant, anti-tumour, anti lipolytic, analgesic, abortifacient, anti-viral, hypoglycemic and immunomodulatory. Medicinal value of bitter melon has been attributed to its high antioxidant properties due in part to phenols, flavonoids, isoflavones, terpenes, anthroquinones, and glucosinolates, all of which confer a bitter taste.  However, oral consumption of bitter gourd products could be a problem due to the bitter taste. Bitter taste should be eliminated. β-cyclodextrin is one of the most common materials used in microencapsulation process. β-cyclodextrin comprises seven units of glucopyranose. An attempt studied the feasibility of bitterness reduction in bitter gourd dried powder by treatment of blanching (100oC in 10s; 95oC in 15s, 90oC in 20s, 85oC in 25s), enzyme (florosil 2g/100ml and naringinase 8 mg/100ml), and wall material (β-cyclodextrin, sodium alginate, carrageenan, pectin). Reduction of bitterness and enhancing palatability are obviously observed by treatment of Momordica charantia dried powder by blanching 100oC in 10s, enzymatic treatment with florosil (2g/100ml) + naringinase (8 mg/100ml) and spray drying at inlet temperature 155oC, out let temperature 85oC, feed rate 15 ml/min with β-cyclodextrin 0.5% as wall material. Keywords: Momordica charantia, Dried powder, Bitterness, β‐cyclodextrin.